Influence and change: a study of the ethical decision making of trainee accountants - Hull, Alison Katherine (1999)
This thesis is concerned with the subject of ethical decision making. A large number of theoretical models of ethical decision making have been developed in recent years. Apart from a small number of studies, there has been very little empirical testing of the theoretical frameworks. Even fewer studies have examined ethical decision making in a longitudinal framework. This thesis defines and extends a part of one of the models, and tests it longitudinally. The longitudinal context allows dynamic issues in ethical decision making to be explored - how ethical decision making changes over time in response to various individual and situational factors. An important debate in the ethical decision making literature concerns the appropriate conceptual basis for ethical judgement. Most previous studies have focused either on the Cognitive Moral Development construct from psychology or on moral philosophy as the root of ethical judgement. This study develops existing theory to accommodate a third basis, that of personal values. The results of the study show that the personal values construct has significant explanatory power. Further, they suggest that it offers an attractive avenue by which researchers can further explore the relationships between the individual and the organisation.